Periungual basal cell carcinoma - Laura Loures Tavares; Juliana Corrêa Marques da Costa; Nathália Carvalho Delcourt; Nilton Carlos dos Santos Rodrigues (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Periungual basal cell carcinoma is rare and needs to be differentiated from other common diseases that affect this region. Several factors are associated with the development of this tumor, and sun damage seems to play an important role in its pathogenesis. Dermoscopy of clinically indolent lesions on the nail unit can shorten the diagnostic process and avoid destructive treatment and functional damage.